2015
DOI: 10.1093/rheumatology/kev253
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of major salivary glands: a highly specific tool for distinguishing primary Sjögren’s syndrome from undifferentiated connective tissue diseases

Abstract: This study confirmed the good sensitivity and the high specificity of SGUS in differentiating SS from other CTDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…El Miedany et al identified in their study a significant correlation between the salivary gland ultrasound score and the histopathological score (r = 0:82, p < 0:001) [30]. Using the ultrasonographic scoring system described by De Vita et al, Luciano et al described a significant correlation between the SGUS score and the minor salivary gland biopsy/focus score (r = 0:484, p < 0:0001) [31]. Analyzing retrospectively the records of 85 suspected pSS patients, Astorri et al identified that an overall concordance between the ultrasound and the histology was 91% [32].…”
Section: Disease Markersmentioning
confidence: 95%
“…El Miedany et al identified in their study a significant correlation between the salivary gland ultrasound score and the histopathological score (r = 0:82, p < 0:001) [30]. Using the ultrasonographic scoring system described by De Vita et al, Luciano et al described a significant correlation between the SGUS score and the minor salivary gland biopsy/focus score (r = 0:484, p < 0:0001) [31]. Analyzing retrospectively the records of 85 suspected pSS patients, Astorri et al identified that an overall concordance between the ultrasound and the histology was 91% [32].…”
Section: Disease Markersmentioning
confidence: 95%
“…Patients diagnosed with Sjögren's syndrome according to the AECG criteria presented with higher SGUS score compared with patients with UCTD. Setting the SGUS cut‐off score at a value of >2 provided a sensitivity of 65%, a specificity of 96%, a positive predictive value of 95%, and a negative predictive value of 73% for the diagnosis of Sjögren's syndrome .…”
Section: Major Salivary Gland Ultrasonographymentioning
confidence: 99%
“…The presence of multiple ovoid hypoechoic lesions, often bounded by hyperechoic bands, correlates with markers of more severe disease. These imaging abnormalities have high specificity for the diagnosis, but only moderate sensitivity [50-54]. …”
Section: Diagnosis Of Sjögren's Syndromementioning
confidence: 99%